Features Of The Choice Of Applicable Law To Industrial Property - Shakhnazarov, Beniamin A. (Opción, 2019)
The study deals with applying conflict of laws mechanisms to legal regulation of industrial property rights protection. The work considers the provisions of the congruent principles of conflict of laws regulation of intellectual property developed by the world’s leading scientific centers (ALI, CLIP, TRANSPARENCY, WASEDA, KOPILA principles), taking into account the industrial property specifics. It is proposed to apply the law of the country, for which protection is sought, to solve the issues of protected industrial property and related formalities. For all other matters of the immaterial statute, the appli- cable law is the law of each country of registration.